Jeux de pères. La conversion de paternité dans quelques images médiévales - Jérôme Baschet (Images Re-Vues)
As medieval Christianity sees itself as a hierarchized kin system organized in networks (carnal kinship, spiritual kinship, divine kinship), a religious conversion has to be, at the same time, a kinship conversion. Leaving carnal fatherhood behind in order to endorse divine fatherhood fully (and brotherhood with fellow Christians): such is the formula that can be traced through historical variations, since evangelical and patristic times till the Middle Ages. The most important transformations concern the role of the mother figure and the intensity and conflicts between different levels of kinship. This article studies the conversion of Francis of Assisi from this point of view, with an emphasis on the frescoes by Giotto, which offer an exceptional geometrization of medieval kin system. By confronting different iconographical versions of the conversion of the saint, one can understand how much the articulation between the three fatherhoods was an issue in the Franciscan Order, caught between its initial radical rupture and its inscription in Church as an institution.